Serum Calcification Propensity and Calcification of the Abdominal Aorta in Patients With Primary Aldosteronism - Kantauskaite, Marta; Bolten, Katharina; Boschheidgen, Matthias; Schmidt, Claudia; Kolb, Thilo; Eckardt, Kai Uwe; Pasch, Andreas; Schimmöller, Lars; Rump, Lars C.; Voelkl, Jakob; Stegbauer, Johannes (Frontiers in Cardiovascular Medicine, 2022)
Patients with primary aldosteronism (PA) are more susceptible to cardiovascular disease and mortality than patients with primary hypertension. This is mostly attributed to excess production of aldosterone and its effects on the development of vascular injury. A novel functional test (T50) measures serum calcification propensity. Lower T50-values predict higher cardiovascular risk. We investigated serum calcification propensity and vascular calcification in PA and resistant hypertension (RH). T50 measurement was performed in patients with PA (n = 66) and RH (n = 28) at baseline and after 403 (279–640) and 389 (277–527) days of treatment. No significant differences in T50-values were observed between the groups (371 ± 65 and 382 ± 44 min, in PA and RH group, respectively, p > 0.05). However, higher aldosterone-to-renin ratios were associated with lower T50-values in PA-patients (r −0.282, p < 0.05). Furthermore, lower T50-values were associated with increased abdominal aortic calcification measured by Agatston score in PA (r −0.534, p < 0.05). In both, PA and RH, higher atherosclerotic cardiovascular disease (ACSVD) scores (r −0.403, p < 0.05) and lower HDL (r 0.469, p < 0.05) was related to lower T50-values in a linear regression model. Adrenalectomy or medical treatment did not increase T50-values. In comparison to patients with stable T50-values, PA patients with a decrease in T50 after intervention had higher serum calcium concentrations at baseline (2.24 ± 0.11 vs. 2.37 ± 0.10 mmol/l, p < 0.05). This decline of T50-values at follow-up was also associated with a decrease in serum magnesium (−0.03 ± 0.03 mmol/l, p < 0.05) and an increase in phosphate concentrations (0.11 ± 0.11 mmol/l, p < 0.05). Resistant hypertension patients with a decrease in T50-values at follow-up had a significantly lower eGFR at baseline. In summary, these data demonstrate an association between a high aldosterone-to-renin ratio and low T50-values in PA. Moreover, lower T50-values are associated with higher ACSVD scores and more pronounced vascular calcification in PA. Thus, serum calcification propensity may be a novel modifiable risk factor in PA.